Stress Distribution in Modified Veneer Crowns: 3D Finite Element Analysis - Madruga, Camila Ferreira Leite [UNESP] (2021)
(1) Background: to propose a new approach for crown veneers, with the use of an aesthetic porcelain coating, only in part of the zirconia infrastructure, and to analyze its biomechanical behavior to minimize chipping failures. (2) Methods: a maxillary molar was modeled using CAD software, preparing for traditional crowns and veneer crowns with various lengths. Five groups were formed: M-control group (monolithic crown of ultra-translucent zirconia); B-conventional (bilayer crown of ultra-translucent zirconia and ceramic covering); V-veneer (ultra-translucent zirconia crown with reduction only in the buccal and application of covering ceramics); V1-ultra-translucent zirconia crown with buccal reduction and 1 mm occlusal extension for covering ceramic application); V1.5-ultra-translucent zirconia crown with buccal reduction and 1.5 mm occlusal extension for application of covering ceramics. A load of 600 N was performed axially to a fossa bottom to simulate parafunction, and 300 N to the cusp tip to obtain the maximum principal stress results. (3) Results: group B showed a higher stress concentration in the occlusal region of the restorations, while the other groups absorbed the stress and dissipated it throughout the crown, presenting a higher stress concentration in the interface region with the tooth. (4) Conclusion: the highly translucent zirconia ceramic only associated with buccal covering ceramic could add aesthetic gain and rigidity to the system and could be a good option to restore maxillary molars in patients who do not have parafunction.